Curcumin-primed periodontal ligament stem cells-derived extracellular vesicles improve osteogenic ability through the Wnt/β-catenin pathway - Lan, Qian; Cao, Jiadong; Bi, Xueting; Xiao, Xin; Li, Dongsheng; Ai, Yilong (Frontiers in Cell and Developmental Biology, 2023)
Curcumin has broad application prospects in the prevention and treatment of periodontal diseases.Periodontal ligament stem cell-derived extracellular vesicles (PDLSC-EV) can effectively promote periodontal tissue regeneration and possess good drug delivery capability. Superior pharmacological effects can be exerted using PDLSC-EV as a curcumin carrier. In the present study, we constructed curcumin-primed PDLSCs-derived extracellular vesicles (Cur-PDLSC-EV) from cell culture supernatants of curcumin-pretreated PDLSCs by ultracentrifugation and investigated their effects on the proliferation, migration, and osteogenic ability of PDLSCs and the corresponding downstream molecular pathways. Our results showed that both Cur-PDLSC-EV and PDLSC-EV promoted osteoblast proliferation and migration. Compared with PDLSC-EV, Cur-PDLSC-EV possessed a more potent pro-osteogenic ability. Moreover, the improved osteogenesis of Cur-PDLSC-EV was related to the activation of the Wnt/β-catenin signaling pathway. This study suggests that Cur-PDLSC-EV can promote osteogenic differentiation by activating Wnt/β-catenin, providing reference bases for the treatment of periodontal diseases.